Proses Penyambungan Untuk Pemasangan Baru Di Odc Pada Kabel Fiber Optik Di Daerah Jakarta Selatan Di Pt Aquila Wijaya Teknik - Rizquloh, Mochamad Ikhsan; Santoso, Dian Budhi (Jurnal Ilmiah Wahana Pendidikan, 2025)
In the modern era, technology has transformed the telecommunication industry in the world, with legacy telecomunikasi becoming data-based telecomunikasi due to the growth of the internet. Fiber optic cables, such as optical distribution cabinets (ODCs), are used for transmitting signals from one point to another. Optical Distribution Cabinets (ODCs) are devices in the FTTH (Fiber to The Home) topology, consisting of connectors, splicing, splitters, pigtails, slots, and other optical passive components. PT. AQUILA WIJAYA TEKNIK is a company that provides construction and infrastructure services, including fiber optic cable installation. To address these issues, it is necessary to install a fiber optic cable using the correct length and height. The study uses observational data collection methods, including focus, exploration, and orientation, to analyze the process of implementing new ODCs in Jakarta Selatan. The results aim to understand the process of ODC installation in Jakarta Selatan. Fiber optic cable termination is a crucial process that involves the use of a core and a fusion splicing technique. The core is soaked in alcohol and then cleaved with a splicing core. The splicing process is called fusion splicing, which involves separating two fibers into a single fiber. The splicing resistance is typically 0.02 dB.. The termination process includes removing the terminal and cable, the sarana sambung kabel, sealing rings, and the sleeve. Fusion splicing techniques include stripping coating with a stripper, stripping the sleeve, and splicing the fiber with a cleaver. The splicer then reassembles the splicer, ensuring the fiber is properly connected. The termination process is completed by removing the splicer and removing the sleeve.